Effectiveness Of Educational Guidelines On Nurses’ Performance Regarding Nephrotic Syndrome Care Of Pediatric Patients At District Hospital - Perveen, Shagufta; Perveen, Kousar; Jabeen, Rubina; Kausar, Syeda Tasneem (Journal of Neonatal Surgery, 2025)
Objective: To assess nurses’ knowledge and practices about the care of nephrotic syndrome among pediatric population Material and Methods: A quasi-experimental study design was utilized to assess the knowledge and practice of nurses about nephrotic syndrome.The population was staff nurses present at the District Health Quarter, Hospital. The calculated sample size is too small to perform the statistical test with good efficacy. After adding 20% dropout rate the sample size was 50. Results: Nurses showed a fairly strong understanding of nephrotic syndrome, with most correct answers falling between 62% and 84%. The topic they answered most accurately was recognizing edema as a common symptom in children, with 84% getting it right. However, fewer nurses (only 62%) correctly identified the importance of a low-sodium diet, highlighting an area where more education may be needed.Knowledge and practices before and after the intervention periods differed significantly (t>1.945, P<0.05). Conclusion: The results unequivocally show that planned training programs greatly improve nurses' clinical practices and understanding of juvenile nephrotic syndrome. Better support for impacted families, early detection of difficulties, as well as more effective treatment are all possible outcomes of these advancements. Sustaining high-quality juvenile nephrotic syndrome treatment requires ongoing training and focused teaching, particularly in areas like nutrition and long-term follow-up